The Role and Popularity of the Chinese Guzheng in Thailand’s Musical Development - Guan, Wang; Punvaratorn, Metee; Phansue, Veera (วารสารศิลปะและวัฒนธรรมลุ่มแม่น้ำมูล, 2026)
This study examines how the Chinese guzheng has developed within Thailand’s musical landscape and how it is learned, adapted, and sustained. Using a qualitative design, the research combines content analysis of documentary materials with fieldwork in Bangkok, including semi-structured interviews, focus groups, and questionnaires from students and parents. The analysis focuses on three objectives : 1) clarifying the guzheng’s cultural role, public recognition, and learning patterns in Thailand; 2) identifying integration approaches in Thai traditional and popular music, especially tuning, arrangement, and collaboration; and 3) developing guidelines for strengthening guzheng education. Findings indicate that guzheng popularity is shaped by the interaction between institutional support and sustained public performance. Integration is most effective when arrangement and ensemble role design take priority over minor technical adjustments. Sustainable development depends on coordinated support across teaching systems, localized curriculum design, and performance platforms. The study proposes a T-L-P model linking Teacher Development, Localized Curriculum, and Performance Integration as a framework for long-term development.